Oyster Mushroom Cultivation Training to Improve the Community Economy in The Village Of Suka Jadi Aceh Tamiang - Siti Balqies Indra; Hanisah Hanisah; Rozalina Rozalina; Fahmy Fadly; Suri Purnama Febri; Teuku Fadlon Haser; Ika Rezvani Aprita; Radhiah Radhiah (Fakultas Pertanian, Universitas Samudra, 2023)
Livelihood diversification is a strategy to reduce the dependence of a person or group on one particular type of livelihood. This is done by developing various types of businesses or different economic activities, so that the source of income does not only come from the same source. This service aims to increase the income of rice farmers through cultivating oyster mushrooms (Pleurotus ostreatus) and reducing the risk of greater losses if failure occurs when cultivating organic rice. This service was carried out in Suka Jadi Village, Banda Mulia, Aceh Tamiang in August 2023. This service included focus group discussions (FGD) with partners, education, and continued with making kumbung, making baglog and caring for oyster mushrooms. After this service is completed, it is hoped that partners will have new skills and businesses to improve the community's economy.